Influence of Instructional Supports on Learning Outcomes among Learners with Autism Spectrum Disorder - Odero, Orao Remi; Onditi, Mary; Wachianga, Washington (Journal of Research &Method in Education (IOSR-JRME), 2018)
The present study investigated the Influence of Instructional Supports on Learning Outcomes among Learners with Autism Spectrum Disorders. The study population comprised 420 teachers and 30 head teachers, 30 deputy head teachers and 360 teachers in the 30 selected special schools in the North Rift and Western regions of Kenya. The study used convergent parallel mixed methods design. The sample size for this study comprised 200 teachers from 25 schools. Simple random and purposive sampling was used to sample the participants. Data was collected through a survey comprising self-administered questionnaires; in-depth interviews, and classroom observations. Face and construct validity was ensured using expert judgment by university supervisors while reliability was ensured by split-half method and an r=0.858 was reported. Quantitative data was analyzed using descriptive statistics and also inferential statistics such as Pearson Correlation and Regression analysis. Qualitative data on the other hand was analyzed by using thematic framework. Reliability was determined by internal consistency and a reliability coefficient of r=0.752 was reported. The finding of the study reported that there was statistically significant, though weak, positive correlation (r=.206, n=138, p=.015) between use of instructional supports and overall learning outcomes. The study recommended that teachers should adopt more peer mediated skills to assist learners with autism to promote sharing and help each other in classroom activities.
Keywords: Instructional Supports; Learning Outcomes; Autism Spectrum Disorders; Special School; Kenya